PENERAPAN METODE OPEN VPN-ACCESS SERVER SEBAGAI RANCANGAN JARINGAN WIDE AREA NETWORK PADA UNIT ECOSYSTEM SERVICE ASSURANCE - Fikri Firmansyah; Mohammad Badrul (Jurnal Techno Nusa Mandiri, 2015)
The development of information technology has developed rapidly from year to year. The use of the Internet as a very useful addition to mediation communications but still has weaknesses in its security. Ecosystem service assurance is one unit of work on solution division convergence PT. Telekomunikasi Indonesia, Tbk. cannot be separated from the use of networks and the Internet for Operational work Units. Kendall faced by the few employees Units Ecosystem Service Assurance often gets assignments meetings and training outside of town. Sometimes employees get into trouble when had to send the data documentation of meetings and training to upload a file in a web application portal Unit Ecosystem Service Assurance by using email, copy and save the file first before uploading, this method is not very safe and effective. needed a way to connect the mobile intranet access with the existing LAN network at the central office in order to perform data access easily and safely. Solutions that can be used for this problem is to build a network Wide Area Network (WAN) technology with Virtual Private network applications that can use Open VPN Access Server. OpenVPN Access Server delivers ease and security in forming a network of a virtual private network